Degree of Polarization of Cathodoluminescence from a (100) GaAs Substrate with SiN Stripes - Daniel T. Cassidy; Philippe Pagnod-Rossiaux; Merwan Mokhtari (Optics, 2024)
Notes on fits of analytic estimations, 2D finite element method (FEM), and 3D FEM simulations to measurements of the cathodoluminescence (CL) and to the degree of polarization (DOP) of the CL from the top surface of a <semantics>(100)</semantics> GaAs substrate with a 6.22 <semantics>μ</semantics>m wide SiN stripe are presented. Three interesting features are found in the DOP of CL data. Presumably these features are noticeable owing to the spatial resolution of the CL measurement system. Comparisons of both strain and spatial resolutions obtained by CL and photoluminescence (PL) systems are presented. The width of the central feature in the measured DOP is less than the width of the SiN, as measured from the CL. This suggests horizontal cracks or de-laminations into each side of the SiN of about 0.7 <semantics>μ</semantics>m. In addition, it appears that deformed regions of widths of ≈1.5 <semantics>μ</semantics>m and adjacent to the SiN must exist to explain some of the features.